2011
DOI: 10.1128/jvi.05147-11
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Frequency and Mechanisms of HIV-1 and HIV-2 RNA Copackaging by Single-Virion Analysis

Abstract: HIV-1 and HIV-2 are derived from two distinct primate viruses and share only limited sequence identity. Despite this, HIV-1 and HIV-2 Gag polyproteins can coassemble into the same particle and their genomes can undergo recombination, albeit at an extremely low frequency, implying that HIV-1 and HIV-2 RNA can be copackaged into the same particle. To determine the frequency of HIV-1 and HIV-2 RNA copackaging and to dissect the mechanisms that allow the heterologous RNA copackaging, we directly visualized the RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
1
25
2
Order By: Relevance
“…4E). These results are consistent with our previous observation that HIV-1 and HIV-2 RNAs can copackage at a low efficiency (21).…”
Section: /Mkatesupporting
confidence: 93%
See 1 more Smart Citation
“…4E). These results are consistent with our previous observation that HIV-1 and HIV-2 RNAs can copackage at a low efficiency (21).…”
Section: /Mkatesupporting
confidence: 93%
“…Construct 1-AAG-BSLMSL is similar to 1-Gag-BSLMSL except that the Gag translational start codon was changed from AUG to AAG to abolish the translation of functional Gag. The previously described construct HIV-2-noGag-BglSL (21) is referred to as 2-noGag-BSL for clarity in the present report; this HIV-2-based construct contains two stop-codon mutations in the gag gene-one at codon 17 of Gag in MA and one at codon 171 of CA-to abolish Gag expression (21). Construct globin-MSL was modified from r-Cfp-betaglobin (27), which encodes a β-globin gene under the control of the tet promoter.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies using electron tomography showed the viral RNPs incorporated in the budding virions possess different lengths; however, only a few virus particles were analyzed, and the segments with similar length could not be differentiated by this method (14,22). The development of single-particle approaches has allowed the characterization of virus particles and events in the virus life cycle that might have been missed in the observations of the entire virus population (23)(24)(25). Therefore, to study the genome packaging of influenza viruses, methods that allow stoichiometric analysis of viral RNAs within single-virus particles with individual RNA sensitivity are required.…”
mentioning
confidence: 99%
“…Interestingly, mutation of core lentiviral cis and trans elements did not improve the efficiency of this technology. Reverse transcriptase mutants V148I and Q151N and complementary DIS mutations did not increase full-length proviral reconstitution, despite reports that they increase the rate of template-switching25262728. This may have been due to impaired infectivity with these variants33 and reduced efficiency of provirus synthesis, despite any increase in recombination frequency.…”
Section: Discussionmentioning
confidence: 69%